Designing and Implementing Corporate Social Responsibility: An Integrative Framework Grounded in Theory and Practice - Maon, François (Journal of business ethics, 2009)
This article introduces an integrative framework of corporate social responsibility (CSR) design and implementation. A review of CSR literature – in particular with regard to design and implementation models – provides the background to develop a multiple case study. The resulting integrative framework, based on this multiple case study and Lewin’s change model, highlights four stages that span nine steps of the CSR design and implementation process. Finally, the study identifies critical success factors for the CSR process.